STUDY REGARDING THE INFLUENCE OF HIKING ON CERTAIN HEALTH MARKERS IN MIDDLE SCHOOL STUDENTS - Dragoi Cristian Corneliu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The aim of this research is to observe the influence the practice of hiking has on the development of certain health markers in the middle school students. This started from the hypothesis stating that the regular practice of hiking can influence favorably certain health markers in these students. The subjects chosen for this study were middle school students who perform regularly mountaineering activities. For the control group, several boys and girls of the same age were chosen who do not practice mountaineering or any other kind of organized athletic activities. The research is a comparative study consisting mainly in applying several tests (the Schellong test, the Ruffier test, thoracic elasticity) envisaging certain somatometric and physiological markers of health. The test led to results, which in turn, after a thorough analysis, led to significant conclusions. Thus, for the Schellong test, both in girls and in boys, the heart rate increase is smaller for the experimental group than for the control group, which indicates a better physiometric marker. For the Ruffier test, even though the compared average values between the two groups are not very high, both being just satisfactory, the experimental group subjects' results are clearly better, indicating another superior physiometric marker. For the thoracic elasticity test, the difference between the average values recorded by the two groups is also in favor of the experimental group, thus this somatometric health marker is also better in that group. Finally, the conclusion is that the regular practice of hiking has favorable influences on certain health markers in middle school students, thus confirming the initial hypothesis.